EDUKASI UTILIZATION OF YARDS FOR FAMILY VEGETABLE NEEDS, AT RT 02, RW 04, JAMBANGAN BARU SELATAN, JAMBANGAN SURABAYA: EDUKASI PEMANFAATAN PEKARANGAN UNTUK KEBUTUHAN SAYUR KELUARGA, DI RT 02, RW 04, JAMBANGAN BARU SELATAN, JAMBANGAN SURABAYA - Sri Hidayati; Sri Purwanti; Nurlina Nurlina; Dwi Puspitasari; Geraldien Geraldien (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
The service carried out by the service team from the Faculty of Agriculture, Universitas Merdeka Surabaya is in RT 02, RW 04, Jambangan Baru Selatan, Jambangan, Surabaya which is located around the Merdeka University Surabaya campus. This area is located in the southern part of Surabaya, and as we know that residential areas in this area have minimal yards. This minimal condition of yard land requires the right strategy and creativity to take advantage of it. The problem is that in the field there are many yards that are left abandoned, so education is needed. this is the main consideration for the implementation team to provide education (knowledge) about the use of yard land to function by growing vegetables that are easy to care for and care for and at low cost, so that household needs for vegetables can be met. Implementation of community service in RT 02, RW 04, Jambangan Baru Selatan, Jambangan, Surabaya in using education and job training methods, which are aimed at increasing knowledge, skills, and attitude targets in optimizing yard land. Provide examples of the implementation of vegetable cultivation at the Faculty of Agriculture, Merdeka University, Surabaya, so that people can cultivate and use their yards properly and correctly. Based on observations made on the implementation of community service in RT 02, RW 04, Jambangan Baru Selatan, Jambangan Surabaya, I am proud, because the people who serve the community are very responsive. So that what was planned by the implementing team together with the local community can be realized very well. By utilizing the home yard for vegetable cultivation, it will also increase the community's ability to manage land properly, as well as one of the fulfillments of community needs